2012
DOI: 10.1104/pp.112.207811
|View full text |Cite
|
Sign up to set email alerts
|

High Light Acclimation in the Secondary Plastids Containing Diatom Phaeodactylum tricornutum is Triggered by the Redox State of the Plastoquinone Pool    

Abstract: In diatoms, the process of energy-dependent chlorophyll fluorescence quenching (qE) has an important role in photoprotection. Three components are essential for qE: (1) the light-dependent generation of a transthylakoidal proton gradient; (2) the deepoxidation of the xanthophyll diadinoxanthin (Dd) into diatoxanthin (Dt); and (3) specific nucleus-encoded antenna proteins, called Light Harvesting Complex Protein X (LHCX). We used the model diatom Phaeodactylum tricornutum to investigate the concerted light accl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
166
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 130 publications
(186 citation statements)
references
References 102 publications
12
166
2
Order By: Relevance
“…1A). This is consistent with the results obtained in P. tricornutum [21]. Moreover, the addition of DCMU significantly reduced the amount and percentage of Dt in HL (Table 1).…”
Section: Influence Of Inhibitors On Npq and The XCsupporting
confidence: 94%
See 1 more Smart Citation
“…1A). This is consistent with the results obtained in P. tricornutum [21]. Moreover, the addition of DCMU significantly reduced the amount and percentage of Dt in HL (Table 1).…”
Section: Influence Of Inhibitors On Npq and The XCsupporting
confidence: 94%
“…It is noteworthy that the NPQ value with DTT treatment was higher than that without DTT during the LL recovery period. These observations are different from the results obtained in the diatom P. tricornutum, where DTT treatment strongly inhibited the induction of NPQ during HL treatment and did not prevent relaxation of NPQ during the LL recovery period [21]. T. pseudonana possesses one DDE and two violaxanthin deepoxidase-like enzymes (VDL) [11].…”
Section: Influence Of Inhibitors On Npq and The XCmentioning
confidence: 65%
“…Most eukaryotic algae have an active xanthophyll cycle (the VAZ cycle or its alternative that involves de-epoxidation of diadinoxanthin (Dd) to diatoxanthin (Dt) (Falkowski and Raven 2007)) as well as proteins homologous to Lhcsr (Niyogi and Truong 2013). In diatoms, antenna-related NPQ is thought to be similar to that in green algae and be driven by structural rearrangements in one of the antenna proteins, Lhcx (Lhcsr homologous) (Bailleul et al 2010;Lavaud et al 2012;Lepetit et al 2013;Goss and Lepetit 2015). Upon DpHdriven de-epoxidation of Dd and protonation of some antenna proteins (presumably Lhcx), PS2 antenna efficiently quenches excited states of chlorophyll a (Lepetit et al 2013;Goss and Lepetit 2015).…”
Section: Introductionmentioning
confidence: 97%
“…In diatoms, antenna-related NPQ is thought to be similar to that in green algae and be driven by structural rearrangements in one of the antenna proteins, Lhcx (Lhcsr homologous) (Bailleul et al 2010;Lavaud et al 2012;Lepetit et al 2013;Goss and Lepetit 2015). Upon DpHdriven de-epoxidation of Dd and protonation of some antenna proteins (presumably Lhcx), PS2 antenna efficiently quenches excited states of chlorophyll a (Lepetit et al 2013;Goss and Lepetit 2015). Additionally NPQ might be accompanied by partial antenna detachment, which may also contribute to overall NPQ through quenching in the detached FCP oligomers (Miloslavina et al 2009;Gundermann and Büchel 2012).…”
Section: Introductionmentioning
confidence: 99%
“…11.1 ; note that in T. pseudonana, Lhcx1 and Lhcx2 encode identical proteins). Transcript levels depend on growth light intensity, whereby, in P. tricornutum, up-regulation under HL is most pronounced for Lhcx2 , followed by Lhcx3 and Lhcx1 (Nymark et al 2009(Nymark et al , 2013Lepetit et al 2013 ). In Chaetoceros neogracile , a centric diatom the genome of which has not been sequenced, Park et al ( 2010 ) found up-regulation of Lhcx genes under HL, which also correlated with Dt accumulation and formation of NPQ.…”
Section: Lhcx Proteins In Centric Versus Pennate Diatomsmentioning
confidence: 98%